2001
DOI: 10.1017/s0266462301107129
|View full text |Cite
|
Sign up to set email alerts
|

Private Pharmacy Practice and Regulation

Abstract: Objectives: The objective of this study was to assess the effectiveness of government regulation of private pharmacy practice in a low-income country.Methods: The intervention comprised inspections of the pharmacies, information, and distribution of documents to drug sellers and sanctions. It was implemented at two different intensity levels, active and regular intervention. The methods used to assess the effect of the interventions were interviews with the district drug inspectors, drug sellers and customers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 25 publications
0
50
0
Order By: Relevance
“…The same study population was used for our study as for the randomised trial 19 . From all 214 licensed private pharmacies in the 14 districts in Savannakhet, 115 pharmacies were selected at random.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same study population was used for our study as for the randomised trial 19 . From all 214 licensed private pharmacies in the 14 districts in Savannakhet, 115 pharmacies were selected at random.…”
Section: Methodsmentioning
confidence: 99%
“…Since 1996, Savannakhet has been one of the five pilot provinces in the National Drug Policy Programme (NDPP) supported by the Swedish International Development Cooperation Agency (Sida). Drug quality is an essential part of the NDPP and the present study was carried out in the ongoing NDPP implementation, which also included a randomised trial on regulatory enforcement, focusing on private pharmacy services 19 . Due to the opportunity that arose to collect drugs in the field, it was decided to undertake the drug-quality study reported here with drug samples from the same pharmacies.…”
Section: Introductionmentioning
confidence: 99%
“…Even when regulations exist, effective enforcement mechanisms are often absent in low- and middle-income countries [125,133]. Therefore, good legislation is not enough.…”
Section: Dual Practicementioning
confidence: 99%
“…Private pharmacies and clinics represent the most recent types of providers [35]. Little is known about the scope or quality of informal providers but studies on licensed and unlicensed pharmacies indicate that there is considerable room for improvement in not only staff knowledge but also drug quality [38-40]. How these providers are perceived by users and the importance ascribed to biomedical drugs as a treatment option are poorly documented.…”
Section: Introductionmentioning
confidence: 99%